Pemanfaatan Media Smart TV Untuk Menguatkan Kreativitas Siswa Pada Mata Pelajaran IPAS di Sekolah Dasar - Aulia Avida Yahya; Elisa; Rohima Pujiyani; Diatun Atmayanti; Muhammad Anwar Sani (STAI AL-AMIN, 2026)
The use of digital technology in learning has great potential to improve the quality of the learning process, including in strengthening student creativity. This research is motivated by the use of Smart TV in grade V, at SDN 25 Mataram as a learning medium for science and natural sciences that is able to present material visually, interactively, and easily understood. This study aims to determine the extent to which the use of Smart TV media can strengthen student creativity in science and natural sciences learning at SDN 25 Mataram. This research uses a qualitative approach with a case study research type, data collection techniques in the form of observation, interviews, and documentation. The results show that Smart TV is used to increase focus, participation, and the ability of students to generate creative ideas. The conclusion of this study confirms that the use of Smart TV plays a significant role in strengthening student creativity in science and natural sciences learning, so it is worthy of continued optimization as a learning medium in elementary schools.